Galla chinensis alleviated liver damage induced by acetaminophen by regulating intestinal microbiota - Li, Xiaocong; Chen, Jiadong; Xu, Chang; Li, Yong; Li, Kun (Frontiers in Microbiology, 2025)
IntroductionDrug-induced liver injury is a common condition of therapeutics and requires solutions other than drugs. Dietary supplements and herbal products have beneficial potential against liver failure and are often associated with changes in intestinal flora. This study was designed to investigate Galla chinensis (GC) potential in alleviating drug-induced liver injury.MethodsThe treatment group and model group were administered 0.5 mL of GC oil daily for 14 days, followed by induction of acute drug-induced liver injury using Acetaminophen (APAP) on the 15th day via intraperitoneal injection. Serum biochemical analysis and intestinal bacteria 16S rRNA sequencing were conducted to explore the anti-drug liver injury activity of GC.ResultsThe results showed that GC treatment alleviated the increased liver organ index caused by APAP. Furthermore, serum biochemical analysis revealed that GC therapy reduced alanine transaminase (ALT) and aspartate transaminase (AST) levels, indicating a protective effect against APAP-induced liver injury. Additionally, GC demonstrated the ability to regulate the diversity and composition of intestinal microbes and help increase the prevalence of beneficial microbes such as Faecalibaculum and Odoribacter while reducing the prevalence of pathogenic bacteria, including Corynebacterium, Rikenella, Bacillus, Phocaeicola, and Alloprevotella.DiscussionOur findings indicate that GC plays a significant role in mitigating drug-induced liver injury by improving gut microbiome composition, reducing plasma ALT and AST levels, and inhibiting oxidative stress and inflammatory responses. The study further demands investigations to make pharmaceutical products to be used as nutraceuticals against drug-induced toxicities.